Copper foil preventing wrinkles from occurring, electrode including the copper foil, secondary battery including the electrode, and method for manufacturing the same

By controlling the crystal orientation of the copper foil and reducing residual stress, the problems of curling, wrinkling or tearing of extremely thin copper foil during the manufacturing process are solved, and the high capacity and stability of the secondary battery are achieved.

CN113924669BActive Publication Date: 2025-04-29SK NEXILIS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080041738.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-21
Filing Date
2020-11-13
Publication Date
2025-04-29
Estimated Expiration
2040-11-13

AI Technical Summary

Technical Problem

The prior art is difficult to prevent curl, wrinkle or tear when manufacturing extremely thin copper foils, affecting the capacity and stability of the secondary battery.

Method used

By controlling the crystal orientation of the copper foil and reducing residual stress, copper foil with residual stress of 0.5 to 25 Mpa was used, and 2 to 20 ppm of carbon (C) was added to the copper foil to adjust the structure and characteristics of the crystal layer.

Benefits of technology

It effectively prevents curling, wrinkling or tearing of copper foil during manufacturing and use, and improves the capacity retention and stability of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113924669B_ABST
    Figure CN113924669B_ABST
Patent Text Reader

Abstract

One embodiment of the present invention provides a copper foil, comprising: a copper layer having a matte surface and a glossy surface; and an anti-rust film disposed on the copper layer, the copper foil having a residual stress of 0.5 to 25 MPa based on an absolute value, the copper layer comprising copper and carbon (C), wherein the content of the carbon (C) in the copper layer is 2 to 20 ppm, the copper layer having a (111) plane, a (200) plane, a (220) plane and a (311) plane comprising crystalline particles, the diffraction intensity of the (220) plane accounting for 10 to 40% of the sum of the diffraction intensities of the (111) plane, the (200) plane, the (220) plane and the (311) plane, and the crystalline particles on the (220) plane have an average particle size of 70 to 120 nm at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper foil which is prevented from wrinkling or curling, an electrode including the copper foil, a secondary battery including the electrode, and a method for manufacturing the same. Background Art

[0002] A secondary battery is a type of energy converter that converts electrical energy into chemical energy and stores it. When electricity is needed, the chemical energy is converted back into electrical energy to generate electricity. Since secondary batteries can be recharged repeatedly, they are also called rechargeable batteries.

[0003] Among such secondary batteries, lithium secondary batteries have high operating voltage, high energy density and excellent life characteristics. In recent years, with the popularization of portable electronic devices such as smart phones and notebooks and the commercialization of electric vehicles, the demand for lithium secondary batteries has increased rapidly. Such secondary batteries include a negative electrode collector made of copper foil, in which electrolytic copper foil is widely used as a negative electrode collector of secondary batteries. As the demand for secondary batteries increases, the demand for secondary batteries with high capacity, high efficiency and high quality increases, and therefore, a copper foil capable of improving the characteristics of secondary batteries is needed. In particular, a copper foil capable of ensuring high capacity and stable capacity retention of secondary batteries is needed.

[0004] On the other hand, the thinner the copper foil is, the more active material can be contained in the same space, and the number of collectors can be increased, thereby increasing the capacity of the secondary battery. However, as the copper foil becomes thinner, curling occurs, and when the copper foil is rolled up, the edge portion curls, causing defects such as tearing or wrinkling of the copper foil, so it is difficult to manufacture copper foil in the form of very thin films. Therefore, in order to manufacture copper foil with a very thin thickness, it is necessary to prevent the curling of the copper foil.

[0005] On the other hand, the electrolytic copper foil used as the negative electrode current collector has a thickness of about 30 to 40 kgf / mm 2 In order to manufacture high-capacity lithium secondary batteries, metal or composite active materials with high capacity characteristics have recently attracted much attention. Metal or composite active materials expand significantly during the charge and discharge process, so copper foil must be able to cope with the volume expansion of the active material.

[0006] Taking these points into consideration, the copper foil should not be curled, wrinkled or torn, not only in the manufacturing process of the copper foil, but also in the manufacturing process of the secondary battery electrode or the secondary battery using the copper foil. In particular, in the winding process of manufacturing the copper foil by the roll-to-roll (RTR) process or the coating process of the active material in the manufacturing process of the secondary battery electrode using the copper foil, the copper foil should not be torn. Summary of the invention

[0007] Problems to be solved by the invention

[0008] The present invention relates to a copper foil that can meet the above-mentioned requirements, an electrode including the copper foil, a secondary battery including the electrode, and a method for manufacturing the copper foil.

[0009] An object of one embodiment of the present invention is to provide a copper foil that does not curl, wrinkle or tear during the manufacturing process even if it has a thin thickness. In addition, an object of one embodiment of the present invention is to provide a copper foil that does not curl, wrinkle or tear during the manufacturing process of a secondary battery electrode or a secondary battery using the copper foil.

[0010] Another embodiment of the present invention aims to provide an electrode for a secondary battery including the copper foil and a secondary battery including the electrode for a secondary battery.

[0011] Another embodiment of the present invention aims to provide a method for producing a copper foil that prevents curling, wrinkling, or tearing.

[0012] In addition to the above-mentioned modes of the present invention, other features and advantages of the present invention are described below or can be clearly understood by those skilled in the art to which the present invention belongs through these descriptions.

[0013] Technical solutions to the problem

[0014] One embodiment of the present invention is to control the crystal orientation of the copper layer constituting the copper foil to control the curling phenomenon of the copper foil. In addition, it is also intended to reduce the residual stress inside the copper foil to minimize the curling of the copper foil.

[0015] To this end, one embodiment of the present invention provides a copper foil, comprising a copper layer having a matte surface and a glossy surface; and an anti-rust film, disposed on the copper layer, and the copper foil has a residual stress of 0.5 to 25 MPa based on an absolute value, the copper layer contains copper and carbon (C), the content of the carbon (C) in the copper layer is 2 to 20 ppm, the copper layer has a (111) plane, a (200) plane, a (220) plane and a (311) plane comprising crystalline particles, the diffraction intensity of the (220) plane accounts for 10 to 40% of the sum of the diffraction intensities of the (111) plane, the (200) plane, the (220) plane and the (311) plane, and the crystalline particles on the (220) plane have an average particle size of 70 to 120 nm at room temperature.

[0016] The residual stress is measured on at least one of the (111) plane, the (200) plane, the (220) plane, and the (311) plane.

[0017] The residual stress is measured on the (200) plane.

[0018] After heat treatment at 130° C. for 30 minutes, the elongation is 2 to 20%.

[0019] The copper foil has a first surface in the matte surface direction and a second surface in the glossy surface direction, and a difference in surface roughness Ra between the first surface and the second surface is 0.5 μm or less.

[0020] The copper foil has a first surface in the matte surface direction and a second surface in the glossy surface direction, and a difference in surface roughness Rz JIS between the first surface and the second surface is 0.5 μm or less.

[0021] The copper foil has a thickness of 2 to 20 μm.

[0022] The rust-proof film includes at least one of chromium, a silane compound, and a nitrogen compound.

[0023] Another embodiment of the present invention provides an electrode for a secondary battery, comprising the copper foil described above; and an active material layer disposed on at least one side of the copper foil.

[0024] Another embodiment of the present invention provides a secondary battery, comprising: a positive electrode (cathode); a negative electrode (anode), which is arranged opposite to the positive electrode; an electrolyte (electrolyte), which is arranged between the positive electrode and the negative electrode and provides an environment that enables the movement of lithium ions; and a separator (separator), which electrically insulates the positive electrode and the negative electrode, and the negative electrode includes the copper foil and an active material layer arranged on the copper foil.

[0025] Another embodiment of the present invention provides a method for manufacturing a copper foil, comprising: preparing an electrolyte containing copper ions; and 2 ) current density is used to energize an anode plate and a rotating cathode roller arranged in a spaced-apart manner in the electrolyte to form a copper layer, wherein the electrolyte comprises: 70 to 100 g / L of copper ions; 70 to 150 g / L of sulfuric acid; 1 to 45 ppm of chlorine (Cl); 0.6 g / L or less of arsenic (As) ions; 0.01 to 0.1 ml / L of hydrogen peroxide; and an organic additive, wherein the organic additive comprises at least one of a glossing agent (ingredient A), a speed reducer (ingredient B), a leveling agent (ingredient C) and a roughness regulator (ingredient D), wherein the glossing agent (ingredient A) comprises sulfonic acid or a metal salt thereof, the speed reducer (ingredient B) comprises a nonionic water-soluble polymer, the leveling agent (ingredient C) comprises at least one of nitrogen (N) and sulfur (S), and the roughness regulator (ingredient D) comprises a nitrogen-containing heterocyclic quaternary ammonium salt or a derivative thereof.

[0026] The general description of the present invention as above is only for illustrating and explaining the present invention, but not for limiting the scope of rights of the present invention.

[0027] Effects of the Invention

[0028] According to one embodiment of the present invention, the crystal orientation of the copper layer constituting the copper foil is controlled, the residual stress inside the copper foil is reduced, and thus the curling (Curl) of the copper foil is reduced. Thus, curling, wrinkling or tearing is prevented during the manufacturing process of the copper foil. In addition, when such a copper foil is used, curling, wrinkling or tearing of the copper foil is prevented during the manufacturing process of the secondary battery electrode or the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings are used to help the understanding of the present invention and constitute a part of this specification. They illustrate embodiments of the present invention and, together with the summary of the invention, explain the principles of the present invention.

[0030] Figure 1 This is a schematic cross-sectional view of a copper foil according to an embodiment of the present invention.

[0031] Figure 2It is a schematic diagram illustrating the generation of Auger electrons.

[0032] Figure 3 This is an example of an XRD spectrum of copper foil.

[0033] Figure 4 This is an example of an XRD spectrum of residual stress inside a copper foil.

[0034] Figure 5 1 is a schematic cross-sectional view of a copper foil according to another embodiment of the present invention.

[0035] Figure 6 This is a schematic cross-sectional view of a secondary battery electrode according to still another embodiment of the present invention.

[0036] Figure 7 This is a schematic cross-sectional view of a secondary battery electrode according to still another embodiment of the present invention.

[0037] Figure 8 is a schematic cross-sectional view of a secondary battery according to still another embodiment of the present invention.

[0038] Fig. 9 yes Figure 5 Schematic diagram of the manufacturing process of copper foil shown. DETAILED DESCRIPTION

[0039] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0040] It is obvious to those skilled in the art that various changes and modifications can be made to the present invention without exceeding the technical concept and scope of the present invention. Therefore, the present invention includes all changes and modifications within the scope of the invention described in the claims and their equivalents.

[0041] The shapes, sizes, ratios, angles, quantities, etc. disclosed in the accompanying drawings for illustrating the embodiments of the present invention are exemplary, and therefore, the present invention is not limited by the contents shown in the accompanying drawings. Throughout the specification, the same constituent elements may be represented by the same reference numerals.

[0042] When the words "including", "having", "consisting of", etc. are used in this specification, other parts may be added unless the expression "only" is used. When a constituent element is expressed in the singular, the plural number is included unless otherwise explicitly stated. Also, when interpreting a constituent element, it is interpreted as including a tolerance range even if there is no other explicit description.

[0043] When describing the positional relationship, for example, when describing the positional relationship of two parts by using "on ...", "upper ...", "lower ...", "beside ...", etc., one or more other parts may be provided between the two parts, unless the expression "directly" or "directly" is used.

[0044] When describing a temporal relationship, for example, when describing a temporal sequence using "afterwards", "subsequently", "next", "before", etc., discontinuous situations may also be included unless the expression "immediately" or "directly" is used.

[0045] In order to describe various components, expressions such as "first" and "second" are used, but these components are not limited by these terms. These terms are only used to distinguish one component from another component. Therefore, within the technical concept of the present invention, the first component mentioned below may be the second component.

[0046] The term "at least one" should be understood to include all combinations that can be given from more than one of the related items.

[0047] Each feature of each embodiment of the present invention may be partially or entirely combined or combined with each other, may be technically linked and driven in various ways, and each embodiment may be implemented independently of each other, or may be implemented together in an associated relationship.

[0048] Figure 1 1 is a schematic cross-sectional view of a copper foil 101 according to an embodiment of the present invention.

[0049] The copper foil 101 according to an embodiment of the present invention includes a copper layer 110. The copper layer 110 has a matte surface MS and a shiny surface SS opposite to the matte surface MS.

[0050] For example, the copper layer 110 may be formed on the rotating cathode roller by electroplating (see Fig. 9 ). At this time, the smooth surface SS refers to the surface that has been in contact with the rotating cathode roller during the electroplating process, and the matte surface MS refers to the surface on the opposite side of the smooth surface SS.

[0051] Generally, the smooth surface SS has a smaller surface roughness than the matte surface MS. However, an embodiment of the present invention is not limited thereto, and the surface roughness of the smooth surface SS may be equal to or greater than the surface roughness of the matte surface MS. For example, according to the rotating cathode roller 12 (refer to Fig. 9) of the grinding degree, the surface roughness of the smooth surface SS can be less than or greater than the surface roughness (Rz JIS) of the matte surface MS. The surface of the rotating cathode drum 12 can be ground by a grinding brush having a grit ranging from #800 to #3000.

[0052] Reference Figure 1 , the copper foil 101 includes an anti-rust film 211 disposed on the copper layer 110. The anti-rust film 211 may also be omitted.

[0053] The rust-proof film 211 may be disposed on at least one of the matte surface MS and the smooth surface SS of the copper layer 110. Figure 1 The anti-rust film 211 is disposed on the matte surface MS. However, one embodiment of the present invention is not limited thereto, and the anti-rust film 211 may be disposed only on the smooth surface SS, or may be disposed on both the matte surface MS and the smooth surface SS.

[0054] The anti-rust film 211 can protect the copper layer 110, thereby preventing the copper layer 110 from being oxidized or deteriorated during storage or circulation. Therefore, the anti-rust film 211 is also called a protective layer.

[0055] According to an embodiment of the present invention, the anti-rust film 211 may include at least one of chromium (Cr), a silane compound, and a nitrogen compound.

[0056] For example, the rust-proof film 211 may be made of a rust-proof liquid containing chromium (Cr), that is, a rust-proof liquid containing a chromic acid compound.

[0057] According to an embodiment of the present invention, based on the copper layer 110, the copper foil 101 has a first surface S1 as a surface in the matte surface MS direction and a second surface S2 as a surface in the smooth surface SS direction. Figure 1 The first surface S1 of the copper foil 101 is the surface of the anti-rust film 211, and the second surface S2 is the smooth surface SS. According to an embodiment of the present invention, the anti-rust film 211 may also be omitted. When the anti-rust film 211 is omitted, the matte surface MS of the copper layer 110 becomes the first surface S1 of the copper foil 101.

[0058] The copper layer 110 includes copper (Cu) and carbon (C) as a non-copper element. Considering that the non-copper element is a component other than copper contained in the copper layer 110, it can also be called an impurity. Carbon (C) is derived from various organic additives, decomposition products of organic additives, and organic impurities.

[0059] The carbon (C) content of the copper layer 110 is 2 to 20 ppm. When the carbon (C) content is less than 2 ppm, the tendency of grain coarsening is reduced and the curling phenomenon is increased. On the contrary, when the carbon (C) content exceeds 20 ppm, this is a case where an organic additive containing carbon (C) is excessively used, and thus the defects inside the copper foil caused by excessive impurities increase, and the residual stress increases due to uneven internal energy. Therefore, the tensile strength, elongation and conductivity of the copper layer 110 may be reduced.

[0060] The content of carbon (C) contained in the copper layer 110 of the copper foil 101 can be measured by Auger Electron Spectroscopy (AES).

[0061] Figure 2 It is a schematic diagram illustrating the generation of Auger electrons.

[0062] The Auger effect is a physical phenomenon in which an electron emitted by an atom or ion causes another electron to be emitted. The second electron emitted at this time is called an Auger electron.

[0063] When an electron E1 is removed from the inner energy level 1s of an atom and leaves a vacancy, an electron E2 from the higher energy level 2s fills the vacancy and generates energy equal to the energy difference between the higher energy level 2s and the vacancy. The energy thus generated is released in the form of a photon or used to further emit a second electron.

[0064] The phenomenon that the energy released as described above is used for secondary emission and a second electron is emitted to the outside of the atom is called the Auger effect, and the electron emitted at this time is called the Auger electron E. Auger .

[0065] According to an embodiment of the present invention, an argon (Ar) ion beam is irradiated to a sample based on Auger electron spectroscopy (AES), and the content of atoms is detected by analyzing Auger electrons emitted while the sample is etched.

[0066] Specifically, a 2 cm×2 cm measurement sample can be prepared by cutting the copper foil 101, and the number of atoms on the surface of the sample can be measured using PHI700 (ULVAC-PHI, INC.), an Auger Electron Spectroscopy (AES) instrument. The analysis conditions are as follows:

[0067] -Electron Energy Analyzer: CMA (Cylindrical Mirror Analyzer)

[0068] -Electron Beam Energy: 5KeV

[0069] -Target Current: 10nA

[0070] -Tilt: 30 degrees

[0071] -Sputtering Etching Rate: Based on SiO2 (3KV argon ion beam)

[0072] According to one embodiment of the present invention, the copper layer 110 has a crystal plane, and the ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane and (311) plane of the copper layer 110 as crystal planes is 10 to 40%.

[0073] More specifically, the copper layer 110 has a plurality of crystal planes, which can be represented by Miller Index. Specifically, the crystal planes of the copper layer 110 can be represented by (hkl) planes. Each of these crystal planes has a diffraction intensity, and the diffraction intensity of the crystal plane can be measured or calculated using X-ray diffraction (XRD).

[0074] Below, refer to Figure 3 , a method of measuring and calculating the diffraction intensity of the crystal plane of the copper layer 110 constituting the copper foil 101 is described.

[0075] Figure 3 is an example of an XRD spectrum of copper foil. More specifically, Figure 3 This is an XRD spectrum of the copper layer 110 constituting the copper foil 101 . Figure 3 The peaks correspond to the various crystal planes.

[0076] In order to measure the diffraction intensity, first, an XRD spectrum having peaks corresponding to n crystal planes was obtained by X-ray diffraction (XRD) in the diffraction angle range of 30° to 95° (2θ) [target: copper Kα1, 2θ spacing: 0.01°, 2θ scanning speed: 3° / min]. Figure 3 , an XRD spectrum including four peaks corresponding to the (111) plane, the (200) plane, the (220) plane, and the (311) plane is obtained from the copper layer 110. In this case, n is 4.

[0077] Then, the XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) is obtained from the spectrum.

[0078] According to one embodiment of the present invention, the ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane and (311) plane of the copper layer 110 is calculated by the following formula 1.

[0079] [Formula 1]

[0080] The ratio of diffraction intensity of (hkl) plane = 100*I(hkl) / {I(111)+I(200)+I(220)+I(311)}

[0081] If the ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane, and (311) plane is less than 10%, the growth of the (111) plane and the (200) plane in the copper layer 110 is relatively fast, so that the (111) plane and the (200) plane are preferentially oriented, resulting in an excessively fine crystal structure of the copper layer 110 and increased mixing of impurities. As a result, the residual stress of the copper foil 101 increases, which may increase the occurrence of curl in the copper foil 101.

[0082] If the ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane and (311) plane exceeds 40%, the growth of the (111) plane and the (200) plane in the copper layer 110 is relatively slow, so that the microstructure of the copper layer 110 is reduced, thereby reducing the strength of the copper foil 101.

[0083] Therefore, according to one embodiment of the present invention, in the crystal structure of the copper layer 110, the ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, the (200) plane, the (220) plane and the (311) plane is adjusted in the range of 10 to 40%.

[0084] As described above, according to an embodiment of the present invention, curling of the copper foil 101 can be prevented by controlling the crystal orientation of the copper layer 110 , thereby preventing wrinkles from occurring in the copper foil 101 .

[0085] According to an embodiment of the present invention, the copper layer 110 of the copper foil 101 has crystallinity, and each crystal plane (hkl) of the copper layer 110 includes crystalline particles. In other words, the copper layer 110 includes crystalline particles, and the physical and mechanical properties of the copper foil 101 including the copper layer 110 may be different according to the crystallinity of the copper layer 110.

[0086] In one embodiment of the present invention, regardless of whether or not the particles have a specific polyhedral shape, crystalline particles include all particles whose X-ray diffraction phenomenon can be determined by a periodically arranged atomic lattice.

[0087] The crystalline particles included in the copper layer 110 have an average particle size of 70 to 120 nm. More specifically, in a cross section of the copper layer 110 cutting the copper layer 110 in a thickness direction, the average particle size of the crystalline particles is 70 to 120 nm.

[0088] The average particle size of the crystalline particles included in the copper layer 110 can be measured or calculated using the X-ray diffraction (XRD) method described above. The average particle size of the crystalline particles can be calculated by using the half-width of the XRD peak of each crystal plane.

[0089] The half-peak width means, when the relationship between two physical quantities is expressed by a spectrum, that when the shape of the spectrum forms a peak, the value of the vertical axis of the peak is the width of the horizontal axis at half the maximum value of the peak.

[0090] In the case where the crystalline particles included in the copper layer 110 are fine and have a small average particle size, the copper foil 101 can have high strength. Regarding the average particle size of the crystalline particles, the nitrogen (N) component or the sulfur (S) component derived from the organic additive added to the electrolyte is incorporated into the grain structure of the copper layer 110, thereby exhibiting a pinning effect that does not increase the average particle size of the crystalline particles included in the copper layer 110 even after heat treatment.

[0091] For example, when the copper layer 110 is manufactured by electroplating using an electrolyte, if at least one of chain or cyclic organic substances containing at least one of nitrogen (N) and sulfur (S) is added to the electrolyte, the element of the organic substance is incorporated into the copper layer 110. The element incorporated as described above becomes a non-copper component, that is, an impurity, of the copper layer 110. Such non-copper components finely electrodeposit the copper component in the process of forming the copper layer 110 by electroplating, thereby forming the copper layer 110 and the copper foil 101 composed of small crystal grains. Such a copper foil 101 can have high strength characteristics.

[0092] If the average particle size of the crystalline particles contained in the room temperature copper layer 110 is less than 70nm, the growth of the (111) plane and the (200) plane is relatively fast, so that the (111) plane and the (200) plane are preferably oriented, resulting in an excessively fine crystal structure of the copper layer 110 and an increase in the mixing of impurities. As a result, the residual stress of the copper foil 101 increases, which may increase the occurrence of curl in the copper foil 101. On the contrary, if the average particle size of the crystalline particles contained in the copper layer 110 exceeds 120nm, the microstructure of the copper layer 110 decreases, and it is difficult to achieve high strength of the copper foil 101.

[0093] According to an embodiment of the present invention, the copper foil 101 has a residual stress of 0.5 to 25 MPa based on an absolute value.

[0094] Residual stress is the stress that remains inside an object even when no external force is applied to it. Residual stress is the stress generated inside an object that has been processed or heat treated, and depending on the object's processing history, tensile stress or compressive stress can remain in the object. This residual stress can become the cause of destruction or damage to the object.

[0095] When the copper foil 101 has a large residual stress based on an absolute value, the curl of the copper foil becomes serious. Since the curl phenomenon occurs seriously in the copper foil in the form of a thin film, it is particularly important to control the curl phenomenon when manufacturing the copper foil in the form of a thin film.

[0096] According to an embodiment of the present invention, the curling of the copper foil is prevented by adjusting the residual stress of the copper foil.

[0097] Specifically, a positive residual stress indicates tensile stress in the copper foil 101, while a negative residual stress indicates compressive stress in the copper foil 101. The copper foil may have residual stress in the form of tensile stress or compressive stress depending on the composition of organic additives used in the manufacturing process of the copper foil 101.

[0098] If the residual stress of the copper foil 101 is less than 0.5 MPa, the surface of the copper foil 101 may become rough due to uneven crystal cross-sections in the electrodeposition process for forming the copper layer 110. In this case, in the manufacturing process of the secondary battery electrode using the copper foil 101, the active material may not be uniformly applied to the surface of the copper foil 101, and the charge and discharge capacity retention rate or stability of the secondary battery may be reduced.

[0099] In the electroplating process for manufacturing the copper layer 110 constituting the copper foil 101, the copper foil 101 may have a residual stress of 0.5 MPa or more based on an absolute value by partial incorporation of hydrogen or self-growth of crystal grains. If the absolute value of the residual stress of the copper foil 101 exceeds 25 MPa, curling or wrinkling may occur in the copper foil 101 during the manufacturing process of the secondary battery, thereby reducing workability and increasing the defective rate of the secondary battery.

[0100] Therefore, according to one embodiment of the present invention, the residual stress of the copper foil 101 is set to be within the range of 0.5 to 25 MPa based on an absolute value. To this end, the crystal orientation of the copper layer 110 can be adjusted. That is, according to one embodiment of the present invention, the residual stress of the copper foil 101 can be set to be within the range of 0.5 to 25 MPa based on an absolute value by making the ratio of the diffraction intensity of the (220) plane in the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane, and (311) plane of the copper layer 110 10 to 40%.

[0101] The residual stress of the copper foil 101 can be measured from at least one of the crystal planes of the copper layer 110. That is, the residual stress measured from at least one of the crystal planes of the copper layer 110 can be referred to as the residual stress of the copper foil 101. For example, the residual stress of the copper foil 101 can be measured from at least one of the (111) plane, (200) plane, (220) plane, and (311) plane among the crystal planes of the copper layer 110. That is, the residual stress measured on at least one of the (111) plane, (200) plane, (220) plane, and (311) plane can be the residual stress of the copper foil 101.

[0102] According to an embodiment of the present invention, the residual stress of the copper foil 101 can be measured by an X-ray diffraction (XRD) residual stress measuring instrument. More specifically, the residual stress of each crystal plane of the copper layer 110 can be measured by a residual stress measuring instrument using X-ray diffraction (XRD) of the crystal plane of the copper layer 110.

[0103] For example, the residual stress of the copper foil 101 can be measured by using D8 DISCOVER™ manufactured by Bruker Corporation, which is an X-ray diffraction (XRD) residual stress measuring instrument. At this time, the X-ray diffraction analysis conditions can be set as follows.

[0104] Target: 3kW copper (Cu) target X-ray tube

[0105] Output power: 40kV, 40mA

[0106] wavelength:

[0107] Measuring range: 30~100 degrees

[0108] Scanning axis: θ-2θ

[0109] Scanning speed: 2deg / min

[0110] Figure 4 This is an example of an XRD spectrum of residual stress inside a copper foil. Figure 4 In particular, XRD results for measuring the residual stress of the (200) plane of the copper layer 110 are shown.

[0111] When measuring the residual stress, one of the crystal planes of copper is randomly selected, the 2θ value is fixed, and the measurement is performed only while the θ value is rotated 360°. The residual stress can be measured for each of the four main crystal planes of the copper layer 110, namely, the (111) plane, the (200) plane, the (220) plane, and the (311) plane.

[0112] In particular, in the XRD spectrum, the residual stress of the crystal plane with low intensity but high resolution can be measured, and the measured value can be determined as the residual stress of the copper foil 101. For example, the (200) plane of the copper layer 110 has excellent measurement resolution at a large angle and has high reliability. Therefore, the residual stress measured on the (200) plane of the copper layer 110 can be the residual stress of the copper foil 101.

[0113] According to one embodiment of the present invention, the copper foil 101 has an elongation of 2 to 20% after heat treatment at 130°C for 30 minutes. The elongation can be measured using a universal testing machine (UTM) according to the method specified in the IPC-TM-650 Test Method Manual. According to one embodiment of the present invention, an apparatus from Instron can be used. At this time, the width of the sample for elongation measurement is 12.7 mm, the distance between the grips is 50 mm, and the measurement speed is 50 mm / min.

[0114] If the elongation of the copper foil 101 is less than 2% after heat treatment at 130°C for 30 minutes, the copper foil 101 cannot be stretched sufficiently to respond to the large volume expansion of the high-capacity active material when the copper foil 101 is used as a collector of a secondary battery, and there is a risk of tearing. On the contrary, if the elongation is too large, exceeding 20%, the copper foil 101 is easily stretched during the manufacturing process of the secondary battery electrode, and deformation of the electrode may occur.

[0115] In addition, the copper foil 101 may have an elongation of 2 to 20% at a normal temperature of 25±15° C.

[0116] According to an embodiment of the present invention, the difference in surface roughness Ra between the first surface S1 and the second surface S2 of the copper foil 101 is less than 0.5 μm.

[0117] The surface roughness Ra of one embodiment of the present invention is also referred to as the arithmetic mean roughness. The surface roughness Ra is determined as a value obtained by obtaining the sum of the total area from the center line of the measurement interval (reference length) to the top and bottom in the surface roughness profile and dividing the sum by the length of the measurement interval. The surface roughness Ra can be measured using a surface roughness measuring instrument (M300, Mahr) according to the JIS B 0601-2001 standard.

[0118] According to still another embodiment of the present invention, the difference in surface roughness RzJIS between the first surface S1 and the second surface S2 of the copper foil 101 is 0.5 μm or less.

[0119] The surface roughness Rz JIS of another embodiment of the present invention is also called the ten-point average roughness. The surface roughness Rz JIS is determined as follows: the sum of the distances (absolute value) of the 5 points farthest upward from the center line of the sample interval in the surface roughness profile and the sum of the distances (absolute value) of the 5 points farthest downward are added, and the sum is divided by 5. The surface roughness Rz JIS can be measured using a surface roughness measuring instrument (M300, Mahr) according to the JIS B 0601-2001 standard.

[0120] When the difference in surface roughness (Ra or Rz JIS) between the first surface S1 and the second surface S2 of the copper foil 101 exceeds 0.5 μm, when the copper foil 101 is used as a current collector of an electrode for a secondary battery, the active material cannot be uniformly coated on the first surface S1 and the second surface S2 due to the difference in surface roughness (Ra or Rz JIS) between the first surface S1 and the second surface S2. As a result, when the secondary battery is charged and discharged, the electrical and physical properties of the two surfaces S1 and S2 may differ, which may lead to a decrease in the capacity retention rate and life of the secondary battery.

[0121] In addition, according to an embodiment of the present invention, the first surface S1 and the second surface S2 of the copper foil 101 may have a surface roughness (Ra) of 0.80 μm to 1.30 μm, respectively.

[0122] According to one embodiment of the present invention, the copper foil 101 has a thickness of 2 μm to 20 μm. When the copper foil 101 is used as a collector of an electrode in a secondary battery, the thinner the thickness of the copper foil 101, the more collectors can be accommodated in the same space, which is conducive to the high capacity of the secondary battery. However, when the thickness of the copper foil 101 is less than 2 μm, the processability of the secondary battery electrode or the secondary battery using the copper foil 101 is reduced during the manufacturing process.

[0123] On the contrary, in the case where the thickness of the copper foil 101 exceeds 20 μm, the thickness of the secondary battery electrode using the copper foil 101 increases, and due to such thickness, it may be difficult to achieve a high capacity of the secondary battery.

[0124] Figure 5 1 is a schematic cross-sectional view of a copper foil 102 according to another embodiment of the present invention. In order to avoid redundancy, descriptions of components that have already been described will be omitted.

[0125] Reference Figure 5 The copper foil 102 of another embodiment of the present invention includes a copper layer 110 and two anti-rust films 211 and 212 respectively disposed on the matte surface MS and the smooth surface SS of the copper layer 110. Figure 1 Compared with the copper foil 101 shown, Figure 5 The copper foil 102 shown further includes a rust-proof film 212 disposed on the smooth surface SS of the copper layer 110 .

[0126] For convenience of description, of the two rust-proof films 211 and 212 , the rust-proof film 211 disposed on the matte surface MS of the copper layer 110 is referred to as a first protective layer, and the rust-proof film 212 disposed on the smooth surface SS is referred to as a second protective layer.

[0127] In addition, taking the copper layer 110 as a reference, Figure 5 The copper foil 102 shown has a first surface S1 as a surface in the direction of the matte surface MS and a second surface S2 as a surface in the direction of the smooth surface SS. Here, the first surface S1 of the copper foil 102 is the surface of the antirust film 211 disposed on the matte surface MS, and the second surface S2 is the surface of the antirust film 212 disposed on the smooth surface SS.

[0128] According to another embodiment of the present invention, the two anti-rust films 211 and 212 may respectively contain at least one of chromium (Cr), a silane compound, and a nitrogen compound.

[0129] Figure 5 The copper layer 110 of the copper foil 102 shown has a crystalline structure, and the ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane, and (311) plane of the crystalline structure is 10 to 40%.

[0130] The copper foil 102 has a residual stress of 0.5 to 25 Mpa based on an absolute value. The residual stress can be measured for at least one of the (111) plane, (200) plane, (220) plane, and (311) plane among the crystal planes of the copper layer 110. More specifically, the residual stress can be measured for the (200) plane.

[0131] After heat treatment at 130° C. for 30 minutes, the copper foil 102 has an elongation of 2 to 20%, and a difference in surface roughness Ra or surface roughness Rz JIS between the first surface S1 and the second surface S2 of the copper foil 102 is 0.5 μm or less.

[0132] Figure 5 The copper foil 102 has a thickness of 2 to 20 μm.

[0133] Figure 6 1 is a schematic cross-sectional view of a secondary battery electrode 103 according to another embodiment of the present invention. Figure 6 The secondary battery electrode 103 shown can be applied to Figure 8 The secondary battery 105 is shown.

[0134] Reference Figure 6 A secondary battery electrode 103 according to another embodiment of the present invention includes a copper foil 101 and an active material layer 310 disposed on the copper foil 101. Here, the copper foil 101 includes a copper layer 110 and an antirust film 211 disposed on the copper layer 110, and serves as a current collector.

[0135] Specifically, the copper foil 101 has a first surface S1 and a second surface S2, and the active material layer 310 is disposed on at least one of the first surface S1 and the second surface S2 of the copper foil 101. The active material layer 310 may be disposed on the rust-proof film 211.

[0136] Figure 6 Shows the Figure 1 The copper foil 101 is used as an example of a current collector. However, another embodiment of the present invention is not limited to this, and may also be Figure 5 The copper foil 102 shown is used as a current collector of an electrode 103 for a secondary battery.

[0137] In addition, although Figure 6 , the structure in which the active material layer 310 is disposed only on the first surface S1 of the copper foil 101 is shown, but another embodiment of the present invention is not limited thereto, and the active material layer 310 may be disposed on both the first surface S1 and the second surface S2 of the copper foil 101. In addition, the active material layer 310 may also be disposed only on the second surface S2 of the copper foil 101.

[0138] Figure 6 The active material layer 310 shown is made of an electrode active material, and in particular, can be made of a negative electrode active material. Figure 6 The secondary battery electrode 103 shown can be used as a negative electrode.

[0139] The active material layer 310 may include at least one of carbon, metal, metal oxide, and a metal-carbon composite. As the metal, at least one of Ge, Sn, Li, Zn, Mg, Cd, Ce, Ni, and Fe may be used. In addition, the active material layer 310 may include silicon (Si) to increase the charge and discharge capacity of the secondary battery.

[0140] As the secondary battery is repeatedly charged and discharged, the active material layer 310 shrinks and expands alternately, which causes the active material layer 310 and the copper foil 101 to separate, thereby reducing the charge and discharge efficiency of the secondary battery. In particular, the active material 310 containing silicon (Si) expands and shrinks to a greater extent.

[0141] According to another embodiment of the present invention, since the copper foil 101 used as a current collector can shrink and expand corresponding to the shrinkage and expansion of the active material layer 310, the copper foil 101 will not be deformed or torn even if the active material layer 310 shrinks and expands. Thus, separation does not occur between the copper foil 101 and the active material layer 310. Therefore, a secondary battery including such a secondary battery electrode 103 has excellent charge and discharge efficiency and excellent capacity retention rate.

[0142] Figure 7 1 is a schematic cross-sectional view of a secondary battery electrode 104 according to still another embodiment of the present invention.

[0143] A secondary battery electrode 104 according to another embodiment of the present invention includes a copper foil 102 and active material layers 310 and 320 disposed on the copper foil 102. The copper foil 102 includes a copper layer 110 and rust-proof films 211 and 212 disposed on both surfaces of the copper layer 110.

[0144] Specifically, Figure 7 The secondary battery electrode 104 shown includes two active material layers 310 and 320 respectively arranged on the first surface S1 and the second surface S2 of the copper foil 102. Here, the active material layer 310 arranged on the first surface S1 of the copper foil 102 is referred to as the first active material layer, and the active material layer 320 arranged on the second surface S2 of the copper foil 102 is referred to as the second active material layer.

[0145] The two active material layers 310 and 320 may be made of the same material by the same method, or may be made of different materials or by different methods.

[0146] Figure 8 1 is a schematic cross-sectional view of a secondary battery 105 according to another embodiment of the present invention. For example, Figure 8 The secondary battery 105 shown is a lithium secondary battery.

[0147] Reference Figure 8, the secondary battery 105 includes: a positive electrode (cathode) 370; a negative electrode (anode) 340, which is arranged opposite to the positive electrode 370; an electrolyte (electrolyte) 350, which is arranged between the positive electrode 370 and the negative electrode 340 and provides an environment that enables ions to move; and a separator (separator) 360, which electrically insulates the positive electrode 370 and the negative electrode 340. Here, for example, the ions moving between the positive electrode 370 and the negative electrode 340 are lithium ions. The separator 360 separates the positive electrode 370 from the negative electrode 340 to prevent the charge generated at one electrode from moving to the other electrode through the interior of the secondary battery 105 and being consumed uselessly. Figure 6 , the separator 360 is disposed in the electrolyte 350 .

[0148] The positive electrode 370 includes a positive electrode current collector 371 and a positive electrode active material layer 372. As the positive electrode current collector 371, aluminum foil can be used.

[0149] The negative electrode 340 includes a negative electrode current collector 341 and an active material layer 342. The active material layer 342 of the negative electrode 340 contains a negative electrode active material.

[0150] As the negative electrode current collector 341, it is possible to use Figure 1 or Figure 5 The disclosed copper foils 101 and 102. Figure 6 or Figure 7 The secondary battery electrodes 103 and 104 shown can be used as Figure 8 A negative electrode 340 of the secondary battery 105 is shown.

[0151] Below, refer to Fig. 9 , a method for manufacturing the copper foil 102 according to another embodiment of the present invention is specifically described.

[0152] Fig. 9 yes Figure 5 FIG. 1 is a schematic diagram of a method for manufacturing the copper foil 102 .

[0153] In order to manufacture the copper foil 102 , firstly, the electrolyte 11 containing copper ions is prepared. The electrolyte 11 is contained in the electrolytic tank 10 .

[0154] Next, at 30 to 70 ASD (A / dm 2 ) current density is applied to the anode plate 13 and the rotating cathode roller 12 which are spaced apart from each other in the electrolyte 11 to form a copper layer 110. The copper layer 110 is formed by the principle of electroplating. The interval between the anode plate 13 and the rotating cathode roller 12 can be adjusted within a range of 8 to 13 mm.

[0155] If the current density applied between the anode plate 13 and the rotating cathode roller 12 is less than 30 ASD, the grain generation of the copper layer 110 increases, and if it exceeds 70 ASD, the grain refinement is accelerated. More specifically, the current density can be adjusted to 40 ASD or more.

[0156] The surface properties of the smooth surface SS of the copper layer 110 may vary depending on the degree of polishing or grinding of the surface of the rotating cathode drum 12. To adjust the surface properties of the smooth surface SS, for example, a grinding brush having a grit of #800 to #3000 may be used to grind the surface of the rotating cathode drum 12.

[0157] During the formation of the copper layer 110 , the electrolyte 11 is maintained at a temperature of 40 to 70° C. More specifically, the temperature of the electrolyte 11 may be maintained above 50° C. At this time, the physical, chemical, and electrical properties of the copper layer 110 may be controlled by adjusting the composition of the electrolyte 11 .

[0158] According to an embodiment of the present invention, the electrolyte 11 includes 70 to 100 g / L of copper ions, 70 to 150 g / L of sulfuric acid, 1 to 45 ppm of chlorine (Cl), less than 0.6 g / L of arsenic (As) ions, and organic additives.

[0159] In order to smoothly form the copper layer 110 by copper electrodeposition, the copper ion concentration and the sulfuric acid concentration in the electrolyte 11 are adjusted in the range of 70 to 100 g / L and in the range of 70 to 150 g / L, respectively.

[0160] In one embodiment of the present invention, chlorine (Cl) includes all chloride ions (Cl - ) and chlorine atoms present in the molecule. For example, chlorine (Cl) can be used to remove silver (Ag) ions that flow into the electrolyte 11 during the formation of the copper layer 110. Specifically, chlorine (Cl) can cause the silver (Ag) ions to precipitate in the form of silver chloride (AgCl). This silver chloride (AgCl) can be removed by filtration.

[0161] When the concentration of chlorine (Cl) is lower than 1ppm, silver (Ag) ions cannot be removed smoothly. On the contrary, when the concentration of chlorine (Cl) exceeds 45ppm, unnecessary reactions may occur due to excessive chlorine (Cl). Therefore, the concentration of chlorine (Cl) in the electrolyte 11 is controlled within the range of 1 to 45ppm. More specifically, the concentration of chlorine (Cl) can be controlled below 25ppm, for example, can be controlled within the range of 5 to 25ppm.

[0162] In the electrolyte 11, the concentration of arsenic (As) ions is controlled to be 0.05 to 0.6 g / L. More specifically, in the electrolyte 11, the concentration of arsenic (As) ions is controlled to be 0.1 to 0.3 g / L. In the electrolyte 11, arsenic (As) may be present in a trivalent or pentavalent ion state (As 3+ or As 5+ ) exists. Arsenic (As) in the case of pentavalent ions has better adsorption than trivalent ions, so it should be controlled at a lower concentration. Therefore, in the case of arsenic (As) containing pentavalent ions, arsenic ions (As 5+ ) concentration was controlled to be below 0.3 g / L. On the other hand, in the presence of trivalent arsenic ions (As 3+ ), the concentration of arsenic (As) ions is controlled to be below 0.6 g / L. However, one embodiment of the present invention is not limited thereto.

[0163] Arsenic ion (As 5+ ) acts as an accelerator to promote the reduction reaction of copper (Cu) in a certain concentration range. 5+ ) is less than 0.3 g / L, during the formation of the copper layer 110, the (220) plane grows preferentially based on the crystal plane.

[0164] On the other hand, in the case of arsenic ions (As 5+ ) concentration exceeds 0.3 g / L, when Cu 2+ Cu 1 + When reduced to copper (Cu), an insoluble compound is formed, which may cause impurities to be electrodeposited (doped) onto the copper layer 110. 5+ ) concentration is high, during the formation of the copper layer 110, based on the crystal plane, the (311) plane, the (111) plane and the (200) plane can be preferentially grown, while the growth of the (220) plane can be suppressed.

[0165] Therefore, in order to make the ratio of the diffraction intensity of the (220) plane in the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane and (311) plane in the crystal structure of the copper layer 110 reach 10 to 40%, the arsenic ions (As) in the electrolyte 11 are 5+ ) concentration is controlled below 0.3g / L.

[0166] In addition, according to an embodiment of the present invention, for the crystal orientation of the copper layer 110, the concentration of arsenic (As) ions in the electrolyte 11 may be greater than 0.05 g / L. That is, the concentration of arsenic (As) ions in the electrolyte 11 may be 0.05 to 0.6 g / L.

[0167] The organic additive contained in the electrolyte 11 includes at least one of a glossing agent (ingredient A), a speed reducer (ingredient B), a leveling agent (ingredient C), and a roughness regulator (ingredient D). In the electrolyte 11, the organic additive has a concentration of 1 to 150 ppm.

[0168] The organic additive may include two or more of the glossing agent (component A), the speed reducer (component B), the leveling agent (component C), and the roughness regulator (component D), or may include all four components. Even in this case, the concentration of the organic additive is 150 ppm or less. In the case where the organic additive includes all of the glossing agent (component A), the speed reducer (component B), the leveling agent (component C), and the roughness regulator (component D), the organic additive may have a concentration of 10 to 150 ppm.

[0169] The brightener (ingredient A) contains sulfonic acid or a metal salt thereof. The brightener (ingredient A) may have a concentration of 1 to 50 ppm in the electrolytic solution 11 .

[0170] The brightener (component A) increases the charge amount of the electrolyte 11, thereby increasing the copper electrodeposition speed, improving the curling property of the copper foil, and increasing the gloss of the copper foil 102. If the concentration of the brightener (component A) is less than 1 ppm, the gloss of the copper foil 102 is reduced, and if it exceeds 50 ppm, the roughness of the copper foil 102 may be increased and the strength may be reduced.

[0171] More specifically, the brightener (ingredient A) may have a concentration of 5 to 30 ppm in the electrolytic solution 11 .

[0172] For example, the glossing agent may include at least one selected from bis-(3-sulfopropyl)-disulfide disodium salt (SPS), 3-mercapto-1-propanesulfonic acid, 3-(N,N-dimethylthiocarbamoyl)-thiopropanesulfonic acid sodium salt, 3-[(amino-iminomethyl)thio]-1-propanesulfonic acid sodium salt, O-ethyldithiocarbonic acid-S-(3-sulfopropyl)-ester sodium salt, 3-(benzothiazole-2-mercapto)-propyl-sulfonic acid sodium salt, and ethylene dithiodipropyl sulfonic acid sodium salt.

[0173] The moderator (ingredient B) includes a nonionic water-soluble polymer. The moderator (ingredient B) may have a concentration of 5 to 50 ppm in the electrolyte 11 .

[0174] The moderator (ingredient B) reduces the electrodeposition speed of copper, thereby preventing a sharp increase in roughness and a decrease in strength of the copper foil 102. Such a moderator (ingredient B) is also called an inhibitor or a suppressor.

[0175] If the concentration of the moderator (component B) is lower than 5 ppm, the roughness of the copper foil 102 may increase sharply and the strength of the copper foil 102 may decrease. On the other hand, even if the concentration of the moderator (component B) exceeds 50 ppm, the physical properties such as the appearance, gloss, roughness, strength, and elongation of the copper foil 102 are almost unchanged. Therefore, the concentration of the moderator (component B) can be adjusted within the range of 5 to 50 ppm without unnecessarily increasing the concentration of the moderator (component B) to increase the manufacturing cost and waste raw materials.

[0176] For example, the moderator (ingredient B) may include at least one nonionic water-soluble polymer selected from polyethylene glycol (PEG), polypropylene glycol, polyethylene-polypropylene copolymer, polyglycerol, polyethylene glycol dimethyl ether, hydroxyethyl cellulose, polyvinyl alcohol, stearic acid polyethylene glycol ether, and stearyl alcohol polyethylene glycol ether. However, the type of moderator is not limited thereto, and other nonionic water-soluble polymers that can be used to manufacture high-strength copper foil 102 can also be used as moderators.

[0177] The nonionic water-soluble polymer used as the moderator (component B) may have a number average molecular weight of 500 to 30,000. If the number average molecular weight of the moderator (component B) is less than 500, the effect of the moderator (component B) in preventing the increase in roughness and the decrease in strength of the copper foil 102 is minimal, and if it exceeds 30,000, the copper layer 110 may not be easily formed due to the large molecular weight of the moderator (component B).

[0178] More specifically, the nonionic water-soluble polymer used as the moderator (ingredient B) may have a molecular weight of 1,000 to 10,000.

[0179] The leveler (ingredient C) contains at least one of nitrogen (N) and sulfur (S). That is, the leveler (ingredient C) may contain one or more nitrogen atoms (N) or one or more sulfur atoms (S) in one molecule, and may also contain one or more nitrogen atoms (N) and one or more sulfur atoms (S). For example, the leveler (ingredient C) is an organic compound containing at least one of nitrogen (N) and sulfur (S).

[0180] The leveler (component C) prevents excessively high peaks or excessively large protrusions from being formed on the copper layer 110, making the copper layer 110 macroscopically flat. The leveler (component C) may have a concentration of 1 to 20 ppm in the electrolyte 11.

[0181] When the concentration of the leveler (component C) is less than 1 ppm, the strength of the copper foil 102 is reduced, making it difficult to manufacture a high-strength copper foil 102. On the other hand, when the concentration of the leveler (component C) exceeds 20 ppm, the surface roughness of the copper foil 102 is excessively increased, which may reduce the strength, and pinholes or curls appear on the surface of the copper foil 102, making it difficult to separate the copper foil 102 from the winder WR after it is manufactured.

[0182] For example, the leveler (ingredient C) may include thiourea (TU), diethylthiourea, ethylenethiourea, acetylenethiourea, dipropylthiourea, dibutylthiourea, N-trifluoroacetylthiourea, N-ethylthiourea, N-cyanoacetylthiourea, N-allylthiourea, o-tolylthiourea, N,N'-butylenethiourea, thiazolidinethiol, 4-thiazolinethiol, 4-methyl-2- at least one of pyrimidinethiol (4-methyl-2-pyrimidinethiol) and 2-thiouracil (2-thiouracil), 3-(benzotriazole-2-thiol)-pyrosulfate), 2-mercaptopyridine, 3 (5-mercapto-1H-tetrazolyl) benzenesulfonate, 2-mercaptobenzothiazole, lutidine, 2,2'-bipyridine, 4,4'-bipyridine, pyrimidine, pyridazine, pyrimidine, pyrimidine, pyline, oxazole, thiazole, 1-methylimidazole, 1-benzylimidazole, 1-methyl-2-methylimidazole, 1-benzyl-2-methylimidazole, 1-ethyl-4-methylimidazole, N-methylpyrrole, N-ethylpyrrole, N-butylpyrrole, N-methylpyrroline, N-ethylpyrroline, N-butylpyrroline, pyrimidine, purine, quinoline, isoquinoline, N-methylcarbazole, N-ethylcarbazole and N-butylcarbazole.

[0183] The roughness regulator (ingredient D) comprises a nitrogen-containing heterocyclic quaternary ammonium salt or a derivative thereof.

[0184] The roughness adjuster (ingredient D) improves the glossiness and flatness of the copper foil 102. The roughness adjuster (ingredient D) may have a concentration of 0.01 to 50 ppm in the electrolyte solution 11.

[0185] In the case where the concentration of the roughness modifier (component D) is less than 0.01 ppm, the effect of improving the glossiness and flatness of the copper foil 102 may not be exhibited. On the other hand, in the case where the concentration of the roughness modifier (component D) exceeds 50 ppm, there is a problem that the surface gloss of the first surface S1, that is, the matte surface MS direction of the copper foil 102 becomes uneven and the surface roughness increases sharply, and it is difficult to ensure the desired roughness range. More specifically, the roughness modifier (component D) may have a concentration of 3 to 20 ppm in the electrolyte 11.

[0186] The roughness adjuster (ingredient D) may include at least one of the compounds represented by the following Chemical Formulas 1 to 6. Specifically, the roughness adjuster (ingredient D) may include a compound represented by the following Chemical Formula 6.

[0187] [Chemical formula 1]

[0188]

[0189] [Chemical formula 2]

[0190]

[0191] [Chemical formula 3]

[0192]

[0193] [Chemical formula 4]

[0194]

[0195] [Chemical formula 5]

[0196]

[0197] [Chemical formula 6]

[0198]

[0199] In Chemical Formulae 1 to 6, j, k, l, m, and n1 to n6 may each represent a repeating unit, and are integers greater than or equal to 1, and may be the same as or different from each other.

[0200] According to an embodiment of the present invention, the compounds represented by Chemical Formulae 1 to 6 each have a number average molecular weight of 500 to 12,000.

[0201] In the case where the number average molecular weight of the compounds represented by Chemical Formulas 1 to 6 used as the roughness modifier is less than 500, the surface roughness of the copper foil 102 increases due to the high ratio of the monomers. In the case where the content of the roughness modifier is low, the surface roughness of the matte surface MS of the copper layer 110 increases, thereby possibly reducing glossiness and flatness.

[0202] If the number average molecular weight of the compounds represented by Chemical Formulas 1 to 6 exceeds 12,000, the surface roughness variation of copper foil 102 increases. In this case, even if the concentration of other additives is adjusted, it is difficult to suppress the increase in surface roughness variation of copper foil 102 in the matte direction.

[0203] For example, the compounds represented by Chemical Formulae 1 to 6 may be prepared by polymerization or copolymerization using DDAC (Diallyl dimethylammonium chloride).

[0204] As the compound represented by Chemical Formula 1, there are PAS-H-1L (Mw 8500, Nittobo Co.) and the like.

[0205] As the compound represented by Chemical Formula 2, for example, there are PAS-2451 (Mw 30,000, Nittobo Co.), PAS-2401 (Mw 2,000, Nittobo Co.), and the like.

[0206] As the compound represented by Chemical Formula 3, for example, there are PAS-2351 (Mw 25,000, Nittobo Corporation) and the like.

[0207] As the compound represented by Chemical Formula 4, for example, there are PAS-A-1 (Mw 5,000, Nittobo Co.), PAS-A-5 (Mw 4,000, Nittobo Co.), and the like.

[0208] As the compound represented by Chemical Formula 5, for example, there are PAS-J-81L (Mw 10,000, Nittobo Co.), PAS-J-41 (Mw 10,000, Nittobo Co.), and the like.

[0209] As the compound represented by Chemical Formula 6, for example, there are PAS-21 (Mw 5,000, Nittobo Corporation) and the like.

[0210] According to one embodiment of the present invention, the electrolyte 11 containing organic additives may further contain hydrogen peroxide (H2O2). Organic impurities exist in the continuously plated electrolyte 11 due to the organic additives, and the organic impurities are decomposed by treatment with hydrogen peroxide, so that the content of carbon (C) inside the copper foil can be properly adjusted. As the TOC concentration in the electrolyte 11 increases, the amount of carbon (C) elements flowing into the copper layer 110 increases, and accordingly, the amount of all elements separated from the copper layer 110 during heat treatment increases, thereby causing the strength of the copper foil 102 after heat treatment to decrease.

[0211] The amount of hydrogen peroxide added is 0.01 to 0.1 ml per liter of electrolyte. Specifically, it is preferred to add 0.05 to 0.08 ml per liter of electrolyte. When the amount of hydrogen peroxide added is less than 0.01 ml / L, there is almost no effect of decomposing organic impurities, so it is meaningless. When the amount of hydrogen peroxide added exceeds 0.1 ml / L, organic impurities are excessively decomposed, and the effects of organic additives such as glossing agents, speed reducers, leveling agents, and roughness regulators are also suppressed.

[0212] According to an embodiment of the present invention, a certain amount of carbon (C), hydrogen (H), nitrogen (N) or sulfur (S) can be doped into the copper layer 110 by adjusting the concentration of organic additives, especially organic additives containing nitrogen (N) or sulfur (S), added to the electrolyte 11. The crystal orientation of the copper layer 110 can be controlled by such doping.

[0213] The step of forming the copper layer 110 may include at least one of a step of filtering the electrolyte 11 using activated carbon, a step of filtering the electrolyte 11 using diatomaceous earth, and a step of treating the electrolyte 11 with ozone (O 3 ).

[0214] Specifically, in order to filter the electrolyte 11, the electrolyte 11 may be filtered at 35 to 45 m 3 That is, during the electroplating process for forming the copper layer 110, the flow rate can be 35 to 45 m / h. 3 / hour flow rate to remove solid impurities present in the electrolyte 11. At this time, activated carbon or diatomaceous earth can be used.

[0215] In order to maintain the purity of the electrolyte 11, the electrolyte 11 may also be treated with ozone (O3).

[0216] In order to improve the purity of the electrolyte 11 , the copper wire (Cu wire) used as a raw material of the electrolyte 11 may be cleaned.

[0217] According to one embodiment of the present invention, the step of preparing the electrolyte 11 may include: a step of heat treating the copper wire; a step of pickling the heat treated copper wire; a step of water washing the pickled copper wire; and a step of putting the water washed copper wire into sulfuric acid for the electrolyte.

[0218] More specifically, in order to maintain the purity of the electrolyte 11, a high-purity (99.9% or more) copper wire is heat-treated in an electric furnace at 750°C to 850°C to burn off various organic impurities attached to the copper wire, and then the copper wire heat-treated for 10 to 20 minutes is pickled using a 10% sulfuric acid solution, and the pickled copper wire is washed with distilled water, thereby manufacturing copper for the electrolyte 11. The electrolyte 11 can be prepared by putting the washed copper wire into sulfuric acid for the electrolyte.

[0219] According to an embodiment of the present invention, the concentration of total organic carbon (TOC) in the electrolyte 11 is controlled to be less than 200 ppm in order to satisfy the characteristics of the copper foil 102. That is, the electrolyte 11 may have a total organic carbon (TOC) concentration of less than 200 ppm.

[0220] The copper layer 110 manufactured in the manner described above may be cleaned in the cleaning tank 20 .

[0221] For example, acid cleaning for removing impurities such as resin components or natural oxide on the surface of the copper layer 110 and water cleaning for removing the acid solution used in the acid cleaning may be performed in sequence. The cleaning process may also be omitted.

[0222] Then, rust-proof films 211 and 212 are formed on the copper layer 110 .

[0223] Reference Fig. 9 The copper layer 110 is immersed in the rust-proof liquid 31 contained in the rust-proof tank 30, and the rust-proof films 211 and 212 can be formed on the copper layer 110. The rust-proof liquid 31 can contain chromium, and chromium (Cr) can exist in the rust-proof liquid 31 in an ion state.

[0224] The rust-proof liquid 31 may include 1 to 10 g / L of chromium. To form the rust-proof films 211 and 212 , the temperature of the rust-proof liquid 31 may be maintained at 20 to 40° C. The copper layer 110 may be immersed in the rust-proof liquid 31 for about 1 to 30 seconds.

[0225] Furthermore, the rust-proof films 211 and 212 may further contain a silane compound generated by a silane treatment, and may further contain a nitrogen compound generated by a nitrogen treatment.

[0226] The copper foil 102 is manufactured by forming the rust-proof films 211 and 212 .

[0227] Then, the copper foil 102 is cleaned in the cleaning tank 40. This cleaning step may be omitted.

[0228] Then, after the drying step is performed, the copper foil 102 is wound up by a winder WR.

[0229] Hereinafter, the present invention will be specifically described by means of manufacturing examples and comparative examples. However, the following manufacturing examples and comparative examples are only used to help understanding of the present invention, and the scope of rights of the present invention is not limited to the manufacturing examples or comparative examples.

[0230] Production Examples 1-4 and Comparative Examples 1-4

[0231] The copper foil is manufactured using a foil making machine including an electrolytic cell 10, a rotating cathode roller 12 disposed in the electrolytic cell 10, and an anode plate 13 disposed apart from the rotating cathode roller 12. The electrolyte 11 is a copper sulfate solution. The copper ion concentration in the electrolyte 11 is set to 87 g / L, the concentration of sulfuric acid is set to 110 g / L, the concentration of hydrogen peroxide (H2O2) is set to be maintained at 0.05 to 0.08 ml / L, the temperature of the electrolyte is set to 55°C, and the current density is set to 60 ASD.

[0232] In addition, arsenic (As) ions (As 3+ and As 5+ ) concentration, chlorine (Cl) concentration and organic additive concentration are shown in Table 1 below.

[0233] Among the organic additives, bis-(3-sulfopropyl)-disulfide disodium salt (SPS) was used as a glossing agent (ingredient A), polyethylene glycol (PEG) was used as a speed reducer (ingredient B), thiourea (TU) was used as a leveling agent (ingredient C), and a cyclized polymer derived from diallylamine represented by the chemical formula 6 (PAS-21TM, Nittobo Co., Ltd., Mw 5,000) was used as a roughness regulator (ingredient D).

[0234] A current of 60 ASD is applied between the rotating cathode drum 12 and the anode plate 13 to produce the copper layer 110. Then, the copper layer 110 is immersed in a rust-proof liquid for about 2 seconds to perform a chromate treatment on the surface of the copper layer 110 to form rust-proof films 211 and 212, thereby producing the copper foil 102. As the rust-proof liquid, a rust-proof liquid containing chromic acid as a main component is used, and the concentration of chromic acid is 5 g / L.

[0235] As a result, copper foils of Manufacturing Example 1-4 and Comparative Example 1-4 were manufactured.

[0236] [Table 1]

[0237]

[0238] TU: thiourea; PAS-2401: diarylmethylethylammonium ethyl salt-sulfur dioxide copolymer (Mw 2,000, Nittobo Co., Ltd.)

[0239] For the copper foils of Manufacturing Examples 1-4 and Comparative Examples 1-4 manufactured as described above, (i) residual stress, (ii) crystalline particle size on the (220) plane, (iii) the ratio of diffraction intensity on the (220) plane, (iv) carbon (C) content, (v) elongation after heat treatment, (vi) difference in surface roughness (Ra or Rz JIS) between the first surface and the second surface of the copper foil, and (vii) curl of the copper foil were measured.

[0240] In addition, after manufacturing a secondary battery using the copper foil and charging and discharging the secondary battery, (viii) the secondary battery was disassembled to observe whether wrinkles were generated.

[0241] (i) Determination of residual stress

[0242] The residual stress of the copper foil is measured using X-ray diffraction (XRD). More specifically, the residual stress of each crystal plane of the copper layer 110 is measured using X-ray diffraction (XRD).

[0243] The analysis conditions of X-ray diffraction of copper foil at room temperature are as follows.

[0244] Measurement equipment (model name): Bruker D8 DISCOVER

[0245] Target: 3kW copper (Cu) target X-ray tube

[0246] Output power: 40kV, 40mA

[0247] wavelength:

[0248] Measuring range: 30~100 degrees

[0249] Scanning axis: θ-2θ

[0250] Scanning speed: 2deg / min

[0251] Specifically, the residual stress measurement conditions of the crystal plane of the copper layer 110 constituting the copper foil are shown in Table 2 below.

[0252] [Table 2]

[0253] Anode material Cu Kα1 wavelength 1.540598 Kα2 wavelength 1.544426 Kα2 / Kα1 ratio 0.5 Diverging slits Fixed 3.00mm Using a monochromator yes Generator voltage 40 Tube Current 20 Scan axis Psi Scan range -74.75~74.75 Scan step 0.5 Points(No.of points) 299 Scan Type continuous 2θ 89.9805 Omega 44.9903 Phi 0 X 2 Y 4 Z 9.175 Time per step 3

[0254] (ii) Determination of the size of crystalline particles on the (220) plane

[0255] The average particle size of crystalline particles on the (220) plane among the crystal planes constituting the copper layer 110 of the copper foil manufactured in Manufacturing Example 1-4 and Comparative Example 1-4 was measured.

[0256] The average particle size of crystalline particles can be measured or calculated using X-ray diffraction (XRD). The average particle size of crystalline particles can be calculated by using the half-width of the XRD peak of each crystal plane.

[0257] (iii) Determination of the ratio of the diffraction intensity of the (220) plane

[0258] The ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane, and (311) plane as crystal planes constituting the copper layer 110 of the copper foil manufactured in Manufacturing Example 1-4 and Comparative Example 1-4 was measured.

[0259] First, an XRD pattern having peaks corresponding to n crystal planes was obtained by X-ray diffraction (XRD) in the diffraction angle range of 30° to 95° (2θ) [target: copper Kα1, 2θ spacing: 0.01°, 2θ scanning speed: 3° / min]. Figure 3 In the case of the copper layer 110, an XRD spectrum including four peaks corresponding to the (111) plane, the (200) plane, the (220) plane, and the (311) plane, respectively, can be obtained.

[0260] Then, the XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) is obtained from the spectrum.

[0261] The ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, (200) plane, (220) plane, and (311) plane, which are crystal planes of the copper layer 110 , is calculated by the following formula 1.

[0262] [Formula 1]

[0263] The ratio of diffraction intensity of (hkl) plane = 100*I(hkl) / {I(111)+I(200)+I(220)+I(311)}

[0264] (iv) Carbon (C) content

[0265] The copper foils of Manufacturing Examples 1-4 and Comparative Examples 1-4 were cut to prepare 2 cm×2 cm measurement samples, and the number of atoms from the surface of the samples was measured using PHI700 (ULVAC-PHI, INC.), an Auger Electron Spectroscopy (AES) instrument, to calculate the content of the carbon (C) component.

[0266] The analysis conditions were as follows.

[0267] -Electron Energy Analyzer: CMA (Cylindrical Mirror Analyzer)

[0268] -Electron Beam Energy: 5KeV

[0269] -Target Current: 10nA

[0270] -Tilt: 30 degrees

[0271] -Sputtering Etching Rate: Based on SiO2 (3KV argon ion beam)

[0272] (v) Determination of elongation after heat treatment

[0273] The copper foils produced in Manufacturing Example 1-4 and Comparative Example 1-4 were heat-treated at 130° C. for 30 minutes, and then the elongation of the copper foils was measured.

[0274] The elongation is measured using a universal testing machine (UTM) according to the provisions of the IPC-TM-650 Test Method Manual. Specifically, the elongation is measured using a universal testing machine from Instron. The width of the sample for elongation measurement is 12.7 mm, the distance between the grips is 50 mm, and the measurement speed is 50 mm / min.

[0275] (vi) Difference in surface roughness (Ra or Rz JIS) between the first and second surfaces of the copper foil (ΔRa or ΔRz JIS)

[0276] The surface roughness (Ra or Rz JIS) of the first surface S1 and the second surface S2 of the copper foil produced in Manufacturing Examples 1 to 4 and Comparative Examples 1 to 4 was measured using a surface roughness measuring instrument (M300, Mahr) according to JIS B 0601-2001. The difference (ΔRa or ΔRz JIS) between the surface roughness (Ra or Rz JIS) of the first surface S1 and the second surface S2 of the copper foil was calculated using the measurement results.

[0277] (vii) Measurement of curl of copper foil

[0278] The copper foils prepared in Manufacturing Examples 1-4 and Comparative Examples 1-4 were cut into 30 cm widths (30 cm × 30 cm) in the width direction to prepare the samples. After the first surface S1 of the sample, which is the matte surface MS direction, was placed on the support table with the first surface S1 facing upward, the height raised from the support table was measured. The curl value of the copper foil was calculated by calculating the average value of the heights measured at 4 locations of the sample.

[0279] (viii) Observe the occurrence of wrinkles and tears

[0280] 1) Anode manufacturing

[0281] 2 parts by weight of styrene-butadiene rubber (SBR) and 2 parts by weight of carboxymethyl cellulose (CMC) were mixed with 100 parts by weight of commercially available silicon / carbon composite negative electrode material for negative electrode active material, and distilled water was used as a solvent to prepare a slurry for negative electrode active material. The slurry for negative electrode active material was applied to the electrolytic copper foil of manufacturing examples 1 to 4 and comparative examples 1 to 4 with a width of 10 cm using a scraper at a thickness of 40 μm, dried at 120°C, and applied with a 1 ton / cm 2 of pressure, thereby manufacturing a negative electrode for a secondary battery.

[0282] 2) Preparation of electrolyte

[0283] The base electrolyte was prepared by dissolving LiPF6 as a solute at a concentration of 1 M in a non-aqueous organic solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a ratio of 1:2. The non-aqueous electrolyte was prepared by mixing 99.5 wt % of the base electrolyte and 0.5 wt % of succinic anhydride.

[0284] 3) Cathode manufacturing

[0285] Lithium manganese oxide Li 1.1 Mn 1.85 Al 0.05 O4 and lithium manganese oxide o-LiMnO2 having an orthorhombic crystal structure are mixed in a ratio of 90:10 (weight ratio) to produce a positive electrode active material. The positive electrode active material, carbon black, and poly (vinylidene fluoride) [PVDF: Poly (vinylidene fluoride)] as a binder are mixed in a ratio of 85:10:5 (weight ratio), and mixed with NMP as an organic solvent to prepare a slurry. The slurry prepared as described above is applied to both sides of an Al foil having a thickness of 20 μm, and then dried to produce a positive electrode.

[0286] 4) Manufacturing of lithium secondary batteries for testing

[0287] The positive electrode and the negative electrode are arranged in an insulated manner inside the aluminum can, and a non-aqueous electrolyte and a separator are arranged between them, thereby manufacturing a coin-shaped lithium secondary battery. The separator used is polypropylene (Celgard 2325; thickness: 25 μm, average pore size: Porosity: 40%).

[0288] 5) Charging and discharging of secondary batteries

[0289] The lithium secondary battery manufactured as described above was used to drive the battery at a charge voltage of 4.3 V and a discharge voltage of 3.4 V, and was charged / discharged 100 times at a high temperature of 50° C. and a current rate (C-rate) of 0.2.

[0290] 6) Whether wrinkles or tears occur

[0291] After 100 cycles of charge and discharge, the secondary battery was disassembled to observe whether wrinkles or tears occurred in the copper foil. The case where wrinkles or tears occurred in the copper foil was marked as "occurred", and the case where wrinkles or tears did not occur was marked as "none".

[0292] The above test results are shown in Tables 3 and 4.

[0293] [Table 3]

[0294]

[0295] [Table 4]

[0296]

[0297] The following results can be confirmed by referring to Tables 1, 3, and 4. In the copper foil of Comparative Example 1 produced by an electrolyte containing an excessive amount of a leveler (Component C), the (111) plane has a high residual stress, the size of crystalline particles is smaller than the reference value, and curling and tearing occur.

[0298] The copper foil of Comparative Example 2 manufactured by an electrolyte containing an excessive amount of brightener (component A) had high residual stress, and the size of the crystalline particles was smaller than the reference value. In addition, the ratio of the diffraction intensity of the (220) plane, the carbon (C) content, and the elongation after heat treatment were all below the reference value, the difference in surface roughness between the first surface and the second surface was also large, and wrinkles, curls, and tears occurred.

[0299] The copper foil of Comparative Example 3 produced has high residual stress, and the size of the crystalline particles is smaller than the reference value. In addition, the ratio of the diffraction intensity of the (220) plane and the carbon (C) content are below the reference value, the difference in surface roughness between the first surface and the second surface is also large, and curling and tearing occur.

[0300] The copper foil of Comparative Example 4 manufactured by the electrolyte containing excessive chlorine (Cl) had low residual stress, and wrinkles and tears occurred.

[0301] On the other hand, in the copper foil of Production Example 1-4 of the present invention, curls of 20 mm or less occurred, and wrinkles and tears did not occur at all.

[0302] The present invention described above is not limited to the aforementioned manufacturing examples and drawings. It is obvious to those skilled in the art that various substitutions, deformations or changes can be made within the scope of the technical content of the present invention. Therefore, the scope of the present invention is expressed by the claims, and it should be interpreted that all changes or deformations derived from the meaning, scope and equivalent concepts of the claims are included in the scope of the present invention.

[0303] Description of Reference Numerals

[0304] 101, 102: Copper foil

[0305] 211, 212: Anti-rust film

[0306] 310, 320: Active material layer

[0307] 103, 104: Electrodes for secondary batteries

[0308] MS: rough surface

[0309] SS: Smooth

Claims

1. A copper foil, wherein: include: A copper layer having a matte surface and a glossy surface; as well as An anti-rust film is disposed on the copper layer. The copper foil has a residual stress of 0.5 to 25 MPa based on an absolute value, The copper layer comprises copper and carbon C, In the copper layer, the content of carbon C is 2 to 20 ppm, The copper layer has a (111) plane, a (200) plane, a (220) plane, and a (311) plane including crystalline particles. The ratio of the diffraction intensity of the (220) plane to the sum of the diffraction intensities of the (111) plane, the (200) plane, the (220) plane, and the (311) plane is 10 to 40%, At room temperature, the crystalline particles on the (220) plane have an average particle size of 70 to 120 nm. having a first surface in the matte direction and a second surface in the glossy direction, The surface roughness Ra of the first surface and the second surface is 0.98 to 1.23 μm, respectively. The diffraction intensity of the (220) plane is obtained by X-ray diffraction method XRD in the range of diffraction angle 2θ of 30° to 95°, and the XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) is obtained from the XRD spectrum. In the X-ray diffraction method, the target material is copper Kα1, the 2θ spacing is 0.01°, the 2θ scanning speed is 3° / min, and the n is 4.

2. The copper foil according to claim 1, wherein The residual stress is measured on at least one of the (111) plane, the (200) plane, the (220) plane, and the (311) plane.

3. The copper foil according to claim 1, wherein The residual stress is measured on the (200) plane.

4. The copper foil according to claim 1, wherein After heat treatment at 130°C for 30 minutes, the elongation is 2 to 20%.

5. The copper foil according to claim 1, wherein The difference in surface roughness Ra between the first surface and the second surface is 0.5 μm or less.

6. The copper foil according to claim 1, wherein The difference in surface roughness Rz JIS between the first surface and the second surface is 0.5 μm or less.

7. The copper foil according to claim 1, wherein The thickness is 2 to 20 μm.

8. The copper foil according to claim 1, wherein The rust-proof film includes at least one of chromium, a silane compound, and a nitrogen compound.

9. An electrode for a secondary battery, wherein: include: Copper foil; as well as The active material layer is disposed on at least one side of the copper foil. The copper foil is the copper foil according to any one of claims 1 to 8.

10. A secondary battery, wherein: include: positive electrode; A negative electrode, arranged opposite to the positive electrode; An electrolyte, disposed between the positive electrode and the negative electrode, and providing an environment enabling lithium ions to move; as well as A separator to electrically insulate the positive electrode from the negative electrode, The negative electrode comprises: The copper foil according to any one of claims 1 to 8; as well as The active material layer is disposed on the copper foil.

11. A method for producing a copper foil, wherein: include: The step of preparing an electrolyte containing copper ions; as well as 30 to 70ASD (A / dm 2 ) to form a copper layer by electrifying an anode plate and a rotating cathode drum which are arranged in a manner separated from each other in the electrolyte at a current density of , The electrolyte comprises: 70 to 100 g / L of copper ions; 70 to 150 g / L sulfuric acid; 1 to 45 ppm of chlorine Cl; Arsenic As ions below 0.6 g / L; 0.05 to 0.08 ml / L of hydrogen peroxide; and Organic additives, The arsenic As ions include 0.3 g / L or less of pentavalent ions As 5+ , The organic additive includes at least one of a glossing agent (component A), a speed reducer (component B), a leveling agent (component C) and a roughness regulator (component D), The brightener (ingredient A) comprises a sulfonic acid or a metal salt thereof, The moderator (ingredient B) comprises a non-ionic water-soluble polymer, The leveler (ingredient C) contains at least one of nitrogen N and sulfur S, The roughness regulator (ingredient D) comprises a nitrogen-containing heterocyclic quaternary ammonium salt or a derivative thereof.

Citation Information

Patent Citations

  • Electrolytic copper foil and method for producing the same

    CN103911633A

  • KR20190012922A